Bako National Park's Circumstances amid the COVID-19 Pandemic: Perspectives on Biodiversity and Community Well-being - Mohamad Syahrul Nizam Ibrahim; Nurul Ruwaidah Ahamad; Mohd Hairul Mohd Salleh; Modin Ambau; Nur Nabilah Mohd Kamal (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
Bako National Park (BNP) is the oldest and smallest national park in Sarawak, Malaysia and its richness in biodiversity of flora and fauna here is indeed a major attraction for international and local tourists to watch proboscis monkeys. However, this COVID-19 pandemic instigates challenges to tourism development in the BNP because the number of tourists is very low compared to before pandemic season. This also has a huge impact on the local community and wildlife in this area. These new norms bring challenges and benefits to human and nature life. The following photos were taken during our five-day visit to BNP from 24th to 28th August 2020. The purpose of our short visit was to observe the circumstances of BNP in the midst of pandemic by emphasizing the aspects of biodiversity and the well-being of local communities. Thus, the photographs taken describe the situation in this area that elucidate the challenges and benefits to wildlife and community livelihood. Based on this study, it is clear that humans and biodiversity have complex and interdependent relationships with each other that need to emphasized by relevant stakeholders towards social sustainable development